Pengaruh Pelayanan Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada PT. Amanah Finance Di Makassar) - Muh Fadli Noor; Djamali, Hisnol; Lalo, Annas (Insan Cita Bongaya Research Journal, 2023)
Tax compliance is the behavior of a taxpayer in doing all tax obligations and use taxation rights with still sticking to the legislation perpajakan. Regarding tax compliance is often the case the last few years is the emergence of non-compliance with taxation. This non-compliance will lead to avoidance and tax evasion what will cause a reduction in tax revenue to the state treasury Indonesia. The purpouse of this study was to determine the effect of service quality, and tax penalties in compliance WP OP in PT. Amanah Finance Makassar. The samples used were 100 respondents to the method of determining the sample was purposive sampling. The data collection techniques questionnaire. Data analysis technique used is multiple linear regression analysis. The result obtained by the quality of service and tax penalties and significant positive effect on compliance WP OP.